Some new properties of black holes in the quantum Oppenheimer-Snyder model - Shi-Hai Dong; Farokhnaz Hosseinifar; Filip Studnička; Hassan Hassanabadi (Physics Letters B, 2025)
In response to the limitations of the classical Oppenheimer-Snyder model of black holes, we investigate the quantum framework proposed by Lewandowski et al. (2023) [29]. This quantum model incorporates corrections that allow for a detailed analysis of features such as black hole thermodynamics and Hawking radiation. In particular, we focus on the evaporation process and quasi-normal modes, utilizing the Rosen-Morse approximation method. Furthermore, we explore the topology of photon spheres and the thermodynamic topology of the black hole.